Explaining the performance of contract farming in Ghana: The role of self-efficacy and social capital. (July 2016) - Wuepper, David; Sauer, Johannes
Highlights: We investigate the effect of culture on the performance of contract farming in Ghana. Self-efficacy is the belief of a farmer to have the ability to be successful in a given domain. Social capital increases the ability of the farmer to overcome individual constraints. Both self-efficacy and social capital are cultural traits because they have historical roots, respectively the performance of colonial cocoa cooperatives and the influence of Christian missionary schools. These traits are important determinants of contract farming performance and both are self-reinforcing. Abstract: Self-efficacy is the belief of an individual to have the ability to be successful in a given domain. Social capital is the economic value of a person's relationships. In the context of this study, self-efficacy is the belief of a farmer to be able to improve her income with contract farming, which increases her actual ability. Social capital increases the ability of the farmers through social support. We surveyed 400 smallholder pineapple farmers and find that both self-efficacy and social capital are decisive for their successful integration into contract farming. To identify causal effects, we use two instruments, which are also of interest on their own: the historical presence of (1) cocoa cooperatives and (2) Christian missionary schools. During Ghana's colonial period, the British established cocoa cooperatives, which differed in their performance as a function of biogeographic factors and thus persistently shaped the self-efficacy of the farmers. Roughly at the same time, Christian missionaries established missionary schools, which impacted the traditional societies so that social capital decreased. The finding that self-efficacy and social capital are still shaped by historic variables could indicate that these variables are only slowly changing, or that they only do so in the absence of policy intervention. The latter raises the possibility that effective policies could benefit from strong reinforcing feedbacks once self-efficacy and social capital improve.